Fabrication of Optical Fibre Tapers - Mullaney, Kevin; James, Stephen W.; Tatam, Ralph P. (Cranfield University, 2017)
Data concerning the fabrication of tapered optical fibres. Presented in Proc. SPIE 10323, 10323D. channelled_spectrum_development.zip - Evolution of channeled spectrum during tapering of SMF 28 optical fiber, using a CO2 laser as the heat source. OFS_2017_TAPER_FIGURE2.xlsx - The spectral response of a Vosskuhler NIR-300P NIR camera and the Planckian black body radiation curves (dashed lines) for a range of temperatures near the melting point of silica optical fibres. OFS_2017_TAPER_FIGURE4.xlsx - The strain measured bya fibre Bragg gratings and laser power used during the fabrication of a taper.
Keywords: tapered optical fibres'; 'optical fibre sensors'; 'Photonics and Electro-Optical Engineering (excl. Communications)'